Longitudinal changes of swallowing safety and efficiency in infants with spinal muscular atrophy who received disease modifying therapies - Leon‐Astudillo, Carmen; Brooks, Olivia; Salabarria, Stephanie M.; Coker, Mackenzi; Corti, Manuela; Lammers, Jenna; Plowman, Emily K.; Byrne, Barry J.; Smith, Barbara K. (Pediatric pulmonology, 2024)
Background Dysphagia is a common feature of the natural history of patients with spinal muscular atrophy (SMA). Literature regarding swallowing safety and efficiency is scarce in patients with SMA, particularly in the era of newborn screening programs and disease‐modifying therapies. Objective To describe the longitudinal changes of swallowing safety and efficiency in children with SMA who received one or more disease modifying therapies Methods Case series of patients with SMA followed at the University of Florida from 1 May 2019 to 31 December 2022 who had two or more videofluoroscopy swallowing studies (VFSS), with the first being within 30 days of their first treatment. Data extracted from the electronic health record included: neuromotor outcomes, VFSS penetration aspiration scores (PAS), presence of abrnormal oral or pharyngeal residue, clinical history, and timing of disease‐modifying therapies administration. Results Seven subjects were included (five male); three were diagnosed via newborn screen. Median age at diagnosis was 10 days (range: 4–250). Median age at initial VFSS was 29 days (range: 9–246), and age at the last VFSS was 26.1 months (range: 18.2–36.2). All subjects received onasemnogene‐abeparvovec (OA); four received additional therapies. PAS at diagnosis was abnormal in four subjects. Six subjects required feeding modifications after VFSS results. Of these, three had silent aspiration (PAS 8) and three of them improved after treatment. Conclusions Swallowing safety and efficiency can be impaired in patients with SMA despite early treatment. Larger, prospective studies are needed to define optimal timiing of longitudinal instrumental evaluations.